Portal de apoio à gestão da inovação para empresas paranaenses inovadoras - Silvério, Anderson (2008)
The objective of this study was to propose a set of content, services and features for a portal to support Innovation Management for a number of Paranaense Companies. In the context of an eager society and economy by information and knowledge, the portals of knowledge are tools that can be emphasized by allowing their users registering, sharing and reusing the knowledge available. The portals of knowledge may, however, have several outbreaks, and must be defined according to them. This study treats, in specific, of a services and information portal. It was brought forth to support Paranaense Companies in its innovation management, technological priority, which leads to the particular problem of this research: what are the repositories of content, services and features needed for a portal to support innovation management for innovative Paranaense Companies? In order to answer this question, specific objectives had been elected: (i) diagnose the perception of business as the use of resources of knowledge, technology and innovation management, and the importance and use of information sources for innovation, to identify the supporting content, (ii) identify electronic services and features to support the management of technological innovation, capable to be implemented into a portal of this category, and (iii) develop a computational model for a prototype of services and information portal. For the implementation of the first and second goals were used questionnaires with options for closed answers, graduated in scales, with metric application to the results classification. The whole set of the sample had forty-five respondents, mostly involved with RD&I, from forty-one innovative Paranaense Companies. To implement the third goal, were described actions of analysis and modeling of the portal prototype. Among the achievements, there are some content recommendations, the identification of digital services and features, and guidelines for a computational model of the portal. Concerning recommendations of content, had been distinguished: the employment of management practices in monitoring of technological products, encouraging the formation of networks of knowledge and innovation among organizations, the use of innovation as an indicator of competitiveness, technological practices for better utilization of knowledge and other intangible assets, valuation of a cumulative process of knowledge and actions to stimulate innovation. The digital services identified, after validation by the computational model, were: Support for Innovation; Directory Opportunities; Laws, Rules and Reference Documents, Virtual Library of Academic Works; Newsletter; Indicators of Innovation; Thematic Surveying and Technology Management Tools Encyclopedia. Among the guidelines for the computational model of the portal are detached: the using of oriented programming concepts to an object and design patterns to an abstraction of logical layers of the application, the architecture for modules and the users specialization. It was expected that the final product may be useful to the spread of technological information and to the cooperation between agents of innovation, allowing to the Paranaense businesses better management of innovation.